Exploring the role of leaders in enabling adaptive capacity in hospital teams - a multiple case study - Birte Fagerdal; Hilda Bø Lyng; Veslemøy Guise; Janet E. Anderson; Petter Lave Thornam; Siri Wiig (BMC, 2022)
Abstract Background Resilient healthcare research studies how healthcare systems and stakeholders adapt and cope with challenges and changes to enable high quality care. Team leaders are seen as central in coordinating clinical care, but research detailing their contributions in supporting adaptive capacity has been limited. This study aims to explore and describe how leaders enable adaptive capacity in hospital teams. Methods This article reports from a multiple embedded case study in two Norwegian hospitals. A case was defined as one hospital containing four different types of teams in a hospital setting. Data collection used triangulation of observation and interviews with leaders, followed by a qualitative content analysis. Results Leaders contribute in several ways to enhance their teams' adaptive capacity. This study identified four key enablers; (1) building sufficient competence in the teams; (2) balancing workload, risk, and staff needs; (3) relational leadership; and (4) emphasising situational understanding and awareness through timely and relevant information. Conclusion Team leaders are key actors in everyday healthcare systems and facilitate organisational resilience by supporting adaptive capacity in hospital teams. We have developed a new framework of key leadership enablers that need to be integrated into leadership activities and approaches along with a strong relational and contextual understanding.